A 17,000 year history of Andean climatic and vegetation change from Laguna de Chochos, Peru - Bush, M. B.; Hansen, B. C. S.; Rodbell, D. T.; Seltzer, G. O.; Young, K. R.; Leon, B.; Abbott, M. B.; Silman, M. R.; Gosling, W. D. (Journal of Quaternary Science, 2005)
The manifestation of major climatic events such as the timing of deglaciation and whether, or not, the Younger Dryas affected Andean systems has garnered considerable recent attention. Even the Holocene is rapidly emerging as a time of considerable interest in Neotropical palaeoclimatology and palaeoecology. The Holocene of the Neotropics is now revealed as a time of some temperature change with precipitation:evaporation ratios fluctuating markedly. Major changes in lake level, ice-accumulation, and vegetation are indicative of changes both in precipitation and temperature regimes. Although global-scale forcing mechanisms may underlie some of these changes, e.g. the precessional rhythm, other variability appears to be localised. In a record from near the upper forest limit of the eastern Peruvian Andes, pollen, charcoal, and sedimentary data suggest that the deglaciational period from ca. 17 000 to ca. 11 500 cal. yr BP was a period of rapid climatic oscillations, set against an overall trend of warming. A warm-dry event is evident between ca. 9500 and ca. 7300 cal. yr BP, and comparisons with other regional archives suggest that it was regional in scale. A ca. 1500-yr periodicity in the magnetic susceptibility data is evident between 12 000 and 6000 cal. yr BP, reaching a peak intensity during the dry event. A weaker oscillation with a 500–600-yr periodicity is present throughout much of the Holocene. The uppermost sample of the pollen analysis reveals deforestation as modern human land use simplified the landscape.
id: 1015